ANALISIS KESEJAHTERAAN RUMAH TANGGA PEMANEN MADU HUTAN DI TAMAN NASIONAL TESSO NILO DAN SEKITARNYA DI PROVINSI RIAU: Analysis of Households Welfare Forest Honey Harvester in Tesso Nilo National Park and Surroundings in Riau Province - andre susanto, arfan; Qomar, Nurul; Rifai, Ahmad (PERENNIAL, 2022)
The objectives of this study were to determine the Sialang Trees management system in Tesso Nilo National Park and its surroundings, analyze the Sialang management business, analyze the contribution of Sialang management business income to total household income, and analyze the welfare of forest honey harvesters. This research was conducted in Lubuk Kembang Bunga Village, Ukui District, Pelalawan Regency, Riau Province. The informants in this study were 7 families who harvested Sialang Tree in the Tesso Nilo National Park area. The results of this study found that the Sialang Trees management system had been carried out well and harvesting was carried out in a sustainable manner. During a period of one year, three honey harvests were carried out, resulting in a total of 469 kg of honey with a relatively fixed selling price of Rp. 120,000/kg. The net income of honey takers is Rp. 51,834,334/year. The contribution of Sialang management business income to total household income is 16,95%. 57.1% of the members of the Madu Sialang farmer group are classified as already prosperous.